Comparing the caries-preventive effect of two fissure sealing modalities in public health care: a single application of glass ionomer and a routine resin-based sealant programme. A randomized split-mouth clinical trial - SARI KERVANTO-SEPPÄLÄ (IAPD and Blackwell, 2008)
The prevalence of dental caries has been declining during the past decades in industrialized countries, but caries is still a widespread disease of multifactor nature, affecting the vast majority of people throughout the world 1,2